Synthesis, characterization, mechanical and biological properties of biocomposite based on zirconia containing 1393 bioactive glass with hydroxyapatite - Yadav S.; Singh P.; Pyare R. (My University, 2025)
Zirconia substituted 1393 bioactive glass and hydroxyapatite containing biocomposite were synthesized and sintered to investigate their effect on bioactivity and cell proliferation. The substituted bioactive glass was synthesized by the sol-gel method. Afterward, hydroxyapatite (synthesized by co-precipitation method) was mixed with bioglass in different ratios and sintered at two temperatures (600 °C and 1000 °C) to study the effect on phase, bioactivity, cell proliferation, and mechanical strength. In terms of bioactivity, biocomposites show dissolution and apatite formation in SBF. An increase in density and compressive strength was observed due to the incorporation of glass with hydroxyapatite. Cell proliferation was studied by MTT assay over MG63 cell lines and results indicate that an increase in sintering temperature promotes cell proliferation and found maximum for BG_H80 (sintered at 600 °C) and BG_H50 (sintered at 1000 °C). Due to an increase in sintering temperature crystallization in composites improved the density, compressive strength and cell proliferation and became suitable material for biomedical application. © 2020 Elsevier Ltd and Techna Group S.r.l.